2015
DOI: 10.1590/1809-4503201500050005
|View full text |Cite
|
Sign up to set email alerts
|

The effect of prevention methods on reducing sexual risk for HIV and their potential impact on a large-scale: a literature review

Abstract: A spectrum of diverse prevention methods that offer high protection against HIV has posed the following challenge: how can national AIDS policies with high coverage for prevention and treatment make the best use of new methods so as to reverse the current high, and even rising, incidence rates among specific social groups? We conducted a narrative review of the literature to examine the prevention methods and the structural interventions that can have a higher impact on incidence rates in the context of social… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
1
19

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 94 publications
0
24
1
19
Order By: Relevance
“…The use of such substances may have an influence on the difficulty of reducing new cases of HIV. 3,16 Although it did not observe a statistically significant difference, this study identified that 80.7% of the women who reported an inconsistent use of the condom reported having a fixed partner. The 9/12 male condom has always been the main means of preventing the sexual transmission of HIV, but only the use of this barrier method has become insufficient since its use in all sexual relations is not valued among couples in long-term relationships, as they start to trust one another.…”
Section: /12contrasting
confidence: 55%
See 2 more Smart Citations
“…The use of such substances may have an influence on the difficulty of reducing new cases of HIV. 3,16 Although it did not observe a statistically significant difference, this study identified that 80.7% of the women who reported an inconsistent use of the condom reported having a fixed partner. The 9/12 male condom has always been the main means of preventing the sexual transmission of HIV, but only the use of this barrier method has become insufficient since its use in all sexual relations is not valued among couples in long-term relationships, as they start to trust one another.…”
Section: /12contrasting
confidence: 55%
“…2 Despite the advances in clinical and pharmacological research, which has resulted in the creation of a set of new effective methods to prevent sexual transmission of HIV, coupled with the fact that Brazil has one of the best HIV/aids prevention and treatment programs in the world, the feminization process of the epidemic was not contained. [3][4] The increase in the incidence of cases in the female population can be verified by the reduction in the sex ratio over the years. In 1986, for every 15 cases among men, there was one case in woman.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…La demanda de uso de la PEP aumentó, principalmente, entre personas que se identifican como gays y hombres que tienen sexo con otros hombres (9,10,11,12) . Uno de los temores señalados con relación a la PEP es la posibilidad de provocar el aumento de prácticas sexuales de riesgo al VIH y el uso repetido de la estrategia (13) .…”
Section: Introductionunclassified
“…No que tange especificamente aos homens heterossexuais, estes eram menos propensos a procurarem testes de HIV do que os outros homens e mulheres por conta das construções sociais relacionadas à masculinidade hegemônica (BARROS et al, 2017). Ainda assim, no contexto brasileiro, poucos estudos têm se debruçado sobre a TS-HIV entre homens em geral e, mais especificamente entre homens heterossexualmente ativos, apesar de alguns achados qualitativos sugerirem menores taxas de TS-HIV como método preventivo entre brasileiros quando comparado aos homens de países norte-americanos e europeus (GRANGEIRO et al, 2015b;LIU et al, 2014).…”
Section: []unclassified